2003
DOI: 10.1089/109493103322011641
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Computer Games and Virtual Reality in Exposure Therapy for Fear of Driving Following a Motor Vehicle Accident

Abstract: Specific phobia, situational type-driving, induced by accident (accident phobia) occurs in 18-38% of those involved in a vehicular accident of sufficient severity to warrant referral to the emergency departments of a general hospital. The objective is to investigate, in an open study, the effectiveness of the combined use of computer generated environments involving driving games (game reality [GR]) and a virtual reality (VR) driving environment in exposure therapy for the treatment of driving phobia following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
18

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 3 publications
1
68
0
18
Order By: Relevance
“…Thus the interactivity in this example serves not so much to allow the patient to explore different outcomes, but to enable them to initiate outcomes as if they are causing them to occur. There is some evidence from virtual reality research that this sense of immersion and control may increase the intensity of exposures and therefore increase their efficacy (Price and Anderson, 2007;Walshe et al, 2003).…”
Section: An Imaginal Exposure Story In Dinementioning
confidence: 99%
“…Thus the interactivity in this example serves not so much to allow the patient to explore different outcomes, but to enable them to initiate outcomes as if they are causing them to occur. There is some evidence from virtual reality research that this sense of immersion and control may increase the intensity of exposures and therefore increase their efficacy (Price and Anderson, 2007;Walshe et al, 2003).…”
Section: An Imaginal Exposure Story In Dinementioning
confidence: 99%
“…This driving simulation can reduce anxiety felt by patients while driving in virtual world. This study shows that VR is beneficial in treatment of patients with phobia after an accident, even in the most terrifying conditions, such as post-traumatic stress disorder and depression [12].…”
Section: Introductionmentioning
confidence: 70%
“…[61][62][63][64] Also, as mentioned earlier, many games and ''playful interventions'' have been developed for therapeutic purposes. [33][34][35][36][37][38][39][40][41][42][43][44][45] However, the use of games as a tool for cCBT is quite uncommon. In fact, only one study of a game fully integrated into a CBT surrounding was found.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, support has been reported of beneficial effects in the treatment of a variety of complaints, including depression, divorce trauma, autism, and phobias. [33][34][35][36][37][38][39][40][41][42][43][44][45] This article reports a pilot study testing the incremental value in terms of user motivation and treatment effectiveness of ''gamifying'' an existing online CBT-based burnout module.…”
mentioning
confidence: 99%